2012
DOI: 10.1002/ange.201200024
|View full text |Cite
|
Sign up to set email alerts
|

Aus Carbiden abgeleitete Kohlenstoffmonolithe mit hierarchischer Porenarchitektur

Abstract: Sierpinski‐Kohlenstoff: Von makroporösem Carbiden abgeleitete Kohlenstoffmonolithe (DUT‐38) mit einer hierarchischen Porenstruktur aus Mikro‐, Meso‐ und Makroporen, einer großen spezifischen Oberfläche und einem großen Makroporenvolumen wurden hergestellt. Diese Materialien sind ideale Adsorbentien, da hohe Speicherkapazitäten mit exzellenten Adsorptionsraten in der Gasspeicherung und Luftfiltration kombiniert werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Recently,i tw as found that materials havingh ierarchicalporosity exhibit intriguingproperties such as improved mass transport andm inimized diffusion barriers. [23][24][25][26] As far as POPs are concerned, the introductiono fh ierarchical porosity still faces ag reat challenge due to the very limiteds trategies to combine differentlevels of porosity in one POP. [20][21][22] However,s of ar most porous materials with hierarchical porosity are derived from inorganics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,i tw as found that materials havingh ierarchicalporosity exhibit intriguingproperties such as improved mass transport andm inimized diffusion barriers. [23][24][25][26] As far as POPs are concerned, the introductiono fh ierarchical porosity still faces ag reat challenge due to the very limiteds trategies to combine differentlevels of porosity in one POP. [20][21][22] However,s of ar most porous materials with hierarchical porosity are derived from inorganics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Sulfur-based cathodes are comparably low by cost since the active material is abundantly available, exhibit a broad operating temperature range, [ 6 ] and contain an intrinsic protection mechanism against overcharging, which greatly enhances battery safety. [ 12 ] Different polymeric precursor routes, [ 13 ] templating approaches, [ 14 ] and post-synthesis activation [ 15 ] /annealing [ 16 ] procedures can be applied to CDCs to further enhance their properties. In EDLCs such components provide the surface area for the adsorption of electrolyte ions to form the Helmholtz double layer.…”
Section: Introductionmentioning
confidence: 99%
“…Along with fundamentally interesting 0D, 1D, and 2D allotropes, such as fullerenes, nanotubes and graphene, 3D porous carbon architectures are useful in many emerging energy related applications, [1,2] such as battery anodes, electrode materials for supercapacitors, and catalyst supports in fuel cells. [2][3][4][5][6] In addition to their high surface areas and high conductivity, porous carbons are environmentally benign and show many attractive properties. [1,[7][8][9] Among those, activated and templated carbons are the most widely studied, but carbide-derived carbons (CDCs) produced by the thermal or thermochemical removal of metals from carbides have received much attention in the past decade.…”
mentioning
confidence: 99%